Menanamkan Nilai-Nilai Akhlak Mulia Pada Anak Usia Dini Di Rumah Quran Alfatihah Kota Jambi - Nur Anisyah; Ria Maharani; Dini Kausari; Marwah, Siti (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
Qualitative research involving one of the teachers was conducted at the Alfatihah Quran House, Jambi City with the aim of forming noble moral values ​​in early childhood through habituation. Documents, observations and interviews were used to collect data. Data is examined qualitatively by collecting information and making judgments. Based on research findings, Rumah Quran Alfatihah prioritizes moral virtues through habits, namely before and after activities, children should pray, be polite to parents and teachers by greeting and kissing hands, as well as studying and memorizing hadiths about the values ​​of good, noble morals. Research findings show the importance of educating young children at Rumah Quran Alfatihah to uphold noble morals, namely instilling morals towards Allah SWT and other humans. This moral cultivation has gone well and is carried out through example, teaching, habituation and providing motivation. Instilling noble morals through habituation in children, apart from being influenced by their cognitive abilities, is also influenced by their moral development. Good habits are important in the process of moral development, if good habits have been instilled since childhood then good forms of behavior will be reflected in life. And of course the task of educators, in this case parents or teachers, must be to be able to introduce the concepts of right or wrong, good or bad so that later children will understand and better understand the concepts of good and bad.